Pengaruh Pemberian Pakan dengan Formulasi Berbeda Terhadap Pertumbuhan Ikan Nila Salin (Oreochromis niloticus) - Damang Suryanto; Beni Suprianto (Jurnal Airaha, 2021)
This study aims to obtain the optimum formulation for the growth of saline tilapia. This research method used a completely randomized design method (CRD) with 3 treatments and 3 replicates. The feed formulation is based on the percentage of each feed constituent material, namely fish meal: soybean meal: wheat flour and water in treatmen A 11,12:55,55:33,33, B 6,67:58,33:35, and C 31,67:26,66:41,67. The dose of feeding given is 4% of the fish biomass with a frequency of feeding 3 times/day. Feeding with different saline tilapia formulations did not have a significant effect on specific growth rate (SGR), survival rate (SR), and FCR.